Uji Efektivitas Ekstrak Kulit Biji Kakao (Theobroma cacao L.) Terhadap Pertumbuhan Malassezia furfur Secara In Vitro - Fajar Daniswara Montana (2020)
Pityriasis versicolor is a skin disease caused by the fungus Malassezia furfur which is often found in Indonesia. Antifungal drugs are often used to treat fungal infection. However, long-term use of antifungal drugs is relatively more expensive and can have side effects for its users. Cocoa bean shells can be used as an antifungal because it contains flavonoids, saponins, and alkaloids. This study aims to determine the antifungal effectiveness of cocoa bean shells extract on the growth of Malassezia furfur. This research is an experimental laboratory study using cocoa bean shells extract with 25%, 50%, 75%, 100%. Tests carried out by the method of Well Diffusion with Sabouraud Dextrose Agar media. The average diameter of inhibition zone of each variance are 3.42 mm, 4.07 mm, 4.9 mm, 7.3 mm. The results of the Kruskal-Wallis statistical test have a value of p = 0.01, which means that there are differences in the effectiveness of cocoa bean shells extract in inhibiting the growth of M. furfur. Post-Hoc Mann-Whitney analysis showed significant differences in all test groups with p <0.05, except at concentrations of 25% with 50% and 50% with 75% with p> 0.05. Cocoa bean shells extract has weak antifungal effectiveness at concentrations of 25%, 50%, and 75%, while at 100% has moderate effectiveness. Keywords : Antifungal, Pityriasis versicolor, Cocoa bean shells, Well diffusion, Malassezia furfur